Mothers' View on Late Postoperative Pain Management by the Nursing Team in Children After Cardiac Surgery (Revista Latino-Americana de Enfermagem, 2010)
Postoperative pain management in children is a complex, multidimensional and subjective phenomenon. It represents a challenge for children, parents and health professionals. This study aimed to understand how mothers assess their children's pain management by the nursing team in the late postoperative phase of cardiac surgery. Empirical data collection was carried out through semistructured interviews with 17 mothers who accompanied their children. Data were subject to qualitative analysis, revealing that, for the mothers, taking good care results from the confidence they vest in the nursing team and from the observation of the medication interventions this team performs. Not taking good care of their children is a consequence of lack of information or inadequate communication between the team and the mothers. The results of this study permit identifying aspects that strengthen and weaken nursing care for these clients, contributing to the improvement of the delivered care.